Three-terminal nanoelectromechanical switch based on tungsten nitride—an amorphous metallic material. (4th December 2015) - Mayet, Abdulilah M; Hussain, Aftab M; Hussain, Muhammad M
Abstract: Nanoelectromechanical (NEM) switches inherently have zero off-state leakage current and nearly ideal sub-threshold swing due to their mechanical nature of operation, in contrast to semiconductor switches. A challenge for NEM switches to be practical for low-power digital logic application is their relatively large operation voltage which can result in higher dynamic power consumption. Herein we report a three-terminal laterally actuated NEM switch fabricated with an amorphous metallic material: tungsten nitride (WN x ). As-deposited WN x thin films have high Young's modulus (300 GPa) and reasonably high hardness (3 GPa), which are advantageous for high wear resistance. The first prototype WN x switches are demonstrated to operate with relatively low control voltage, down to 0.8 V for an air gap thickness of 150 nm.